Implementing a protocol for a research impact assessment of the Centre for Research Excellence in Stroke Rehabilitation and Brain Recovery - Shanthi Ramanathan; Penny Reeves; Simon Deeming; Julie Bernhardt; Michael Nilsson; Dominique A. Cadilhac; Frederick Rohan Walker; Leeanne Carey; Sandy Middleton; Elizabeth Lynch; Andrew Searles (BMC, 2018)
Abstract Background There is growing recognition that the wider benefits of research (economic, social and health impacts) should be assessed and valued alongside traditional research performance metrics such as peer-reviewed papers. Translation of findings into policy and practice needs to accelerate and pathways to impact need to be better understood. This research protocol outlines a mixed methods study to apply the Framework to Assess the Impact from Translational health research (FAIT) to the Centre for Research Excellence in Stroke Rehabilitation and Brain Recovery (CRE-Stroke). FAIT is purpose-designed to encourage research translation and assess research impact but lacks validation. Methods/Design Phase 1 involves application of the FAIT-modified programme logic model to each CRE-Stroke research stream including identifying process, output and impact metrics, as well as end users of the research. A scoping review will inform potential impacts anticipated from CRE-Stroke. In Phase 2, audit and feedback on achievements against plans will track and encourage research translation. Logic models will be updated to account for changes in the research pathways over time. In Phase 3, three proven methods for measuring research impact - Payback, economic assessment and narratives - will be applied to each research stream and the data triangulated and reported in Phase 4. The feasibility of applying FAIT will also be assessed as part of Phase 3. Discussion Use of prospective, comprehensive research impact frameworks for large interdisciplinary programmes of research is rare. FAIT's application to CRE-Stroke will provide opportunity for the impact of CRE-Stroke to be assessed and a range of impacts beyond standard academic achievements to be reliably reported. The feasibility of FAIT's application will also be assessed and, if necessary, refined. The usefulness of FAIT for encouraging research translation will also be described and may prove useful for other programmes looking to implement a research impact framework.